Upaya Peningkatan Hasil Belajar Ekonomi Melalui Penggunaan Metode Problem Based Learning Pada Siswa Kelas X I SMA Negeri 1 Polanharjo Tahun Ajaran 2015/2016 - PUSPITASARI, NUGRAHENI; , Dr. Wafrotur Rohmah, M.M (2016)
The purpose of this study was to determine whether the application of learning models Problem Based Learning (PBL) can improve learning outcomes of economics in class X 1 SMA Negeri 1 Polanharjo year 2015/2016study this method Classroom Action Research (CAR), which held as many as 2 cycles in which each cycle traversed by four stages, namely: (1) the action planning; (2) implementation of the action; (3) observing the action; and (4) reflection action. The subjects of this study were all students of class X 1 SMA Negeri 1 Polanharjo the academic year 2015/2016 as many as 18 students with a composition of 12 women and 6 men. This research was carried out together with teachers kalobolator economic subjects. Data collection technique used observation, documentation, and testing. The results of the study showed an increase in student learning outcomes can be seen from the students who received grades over minimum completeness criteria (KKM) of (22.22%) increased to (88.88%), whereas in the first cycle increased 33,33% and in cycle 2 increased 55,55% Based on this study, Based on this study, it was concluded that the implementation of Problem Based Learning Teaching Method in economic learning can improve learning outcomes economy.